2016
DOI: 10.2147/ott.s99866
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous chemotherapy combined with intravesical chemotherapy to treat T1G3 bladder urothelial carcinoma after transurethral resection of bladder tumor: results of a retrospective study

Abstract: ObjectiveThe management of stage 1 and grade 3 (T1G3) bladder cancer continues to be controversial. Although the transurethral resection of bladder tumor (TURBT) followed by intravesical chemotherapy is a conservative strategy for treatment of T1G3 bladder cancer, a relatively high risk of tumor recurrence and progression remains regarding the therapy. This study aimed to compare the efficacy of intravenous chemotherapy combined with intravesical chemotherapy versus intravesical chemotherapy alone for T1G3 bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We noticed, in this analysis, six studies used IVC alone in the monotherapy group ( Chen et al, 2013 ; Huang et al 2019a ; Huang et al 2019b ; Zhang et al, 2016 ; Sun et al, 2017 ; Huang et al, 2020 ). Therefore, we made this subgroup analysis to compare the efficacy of IAC + IVC with IVC alone.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…We noticed, in this analysis, six studies used IVC alone in the monotherapy group ( Chen et al, 2013 ; Huang et al 2019a ; Huang et al 2019b ; Zhang et al, 2016 ; Sun et al, 2017 ; Huang et al, 2020 ). Therefore, we made this subgroup analysis to compare the efficacy of IAC + IVC with IVC alone.…”
Section: Resultsmentioning
confidence: 94%
“…A total of 1,539 original publications were retrieved through systematic search, among them 514 were excluded as repeated records. After manual selection for titles, abstracts, and full-text articles, we enrolled seven eligible studies involving 1,247 patients who are pathologically diagnosed with NMIBC after bladder-preserving surgery ( Chen et al, 2013 ; Lian et al, 2019 ; Huang et al, 2019b ; Huang et al, 2019a ; Sun et al, 2017 ; Zhang et al, 2016 ; J; Huang et al, 2020 ). The detailed process of the studies’ selection was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations